PERAN KEPEMILIKAN INSTITUSIONAL DALAM HUBUNGAN MANAJEMEN LABA DAN NILAI PERUSAHAAN - Agus Satrya Wibowo (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2020)
This study aims to prove whether institutional ownership can reduce the impact of earnings management practices on firm value. Earnings management is proxied by accrual management, real activity manipulations based on abnormal production costs and abnormal discretionary expenses. Meanwhile, firm value is proxied by the metrics developed by Rhodes-Kropf et al (2005) which have the advantage of detecting misvaluation. The sample is manufacturing companies on the Indonesia Stock Exchange which have institutional ownership. The research period for 2010-2018 with panel data 410 samples observation. The findings show that institutional ownership can mitigate the effect of earnings management on firm value. Surprisingly, finding is that real activity manipulations based on abnormal discretionary expenses have the potential to destroy firm value. In other words, the market is penalizing the value of the company. These results contribute to the insight that the importance of the role of institutional ownership is to reduce information asymmetry in preventing the destruction of firm value. Furthermore, this finding is a supplement for investors, regulators and researchers in estimating the value relevance and improving the quality of accounting numbers in the context of firm value.